Świąd skóry w przebiegu cholestatycznych chorób wątroby - aktualny stan wiedzy - Lipiński, Patryk; Osiecki, Andrzej; Naorniakowska, Magdalena; Gliwicz, Dorota; Jankowska, Irena (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Pruritus is a frequent manifestation of cholestatic disorders. Authors present the currently available knowledge regarding its pathogenesis and pharmacological treatment.